New Procedures in Pediatric Oncology and Hematology: Too Many Questions - Polina G. Gabay; Sophia A. Dronova (Вопросы современной педиатрии, 2021)
The article presents a legal analysis of the procedure for providing medical care in pediatric oncology and hematology which regulates the provision of medical care to children with neoplasms and diseases of the blood and blood-forming organs and certain disorders involving the immune mechanism. The place of the pediatric oncology and hematology profile in the system of existing regulatory legal acts and the role assigned by the new procedure to the pediatric oncologist are determined. The requirements to the structure of medical organizations providing medical care in pediatric oncology and hematology profile, the procedure of oncological and hematological diseases diagnosis and management are considered. Attention is drawn to the lack of timescales of pediatric oncologist-hematologist consultation and taking biopsic material. The algorithm of medical organizations actions on entering data into information systems is analyzed.First published on the official website of LLC “Faculty of Medical Law” (https://kormed.ru/baza-znaniy/nashi-analiticheskie-zaklyucheniya/ novyy-poryadok-po-detskoy-onkologii-i-gematologii-slishkom-mnogo-voprosov/). Re-published with permission of the copyright holder.